Numerical investigation of the performance of AlGaN/GaN/BGaN double-gate double-channel high electron mobility transistor - Hamida Djelti (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this work, we examine the direct-current (DC) behavior and the radio-frequency (RF) performance of both single-gate simple-channel (SGSC), single-gate double-channel (SGDC) and double-gate double-channel (DGDC) AlGaN/GaN/BGaN high electron mobility transistor (HEMT) with BGaN back-barriers consist of 250 nm gate length. Using Technologie Computer Aided Design (TCAD) Silvaco, our isothermal simulation results reveal that the proposed structure of double-gate double-channel HEMT with BGaN back-barriers (DGDCBB HEMT) increases electron concentration and consequently the saturation drain current, breakdown voltage, the transconductance. On the other hand, decreases the gate leakage current compared to a conventional HEMT and to a double-channel HEMT back-barriers. Furthermore, the proposed double-gate double-channel back-barrier HEMT device shows good cutoff frequency (94 GHz) and a maximum oscillation frequency (170 GHz). These results suggest that double-gate double channel HEMT back-barriers could be useful for high-frequency and high-power microwave applications.